Psychotropic medication use and future unexplained and injurious falls and fracture amongst community-dwelling older people: data from TILDA - Kenny, Rose; Briggs, Robert (My University, 2023)
Purpose: Psychotropic medications (antidepressants, anticholinergics, benzodiazepines, 'Z'-drugs and antipsychotics) are frequently identified as Falls Risk Increasing Drugs. The aim of this study is to clarify the association of psychotropic medication use with future falls/fracture amongst community-dwelling older people. Methods: Participants ≥ 65 years from TILDA were included and followed from Waves 1 to 5 (8-year follow-up). Incidence of falls (total falls/unexplained/injurious) and fracture was by self-report; unexplained falls were falls not caused by a slip/trip, with no apparent cause. Poisson regression models reporting incidence rate ratios (IRR) assessed the association between medications and future falls/fracture, adjusted for relevant covariates. Results: Of 2809 participants (mean age 73 years), 15% were taking ≥ 1 psychotropic medication. During follow-up, over half of participants fell, with 1/3 reporting injurious falls, over 1/5 reporting unexplained falls and almost 1/5 reporting fracture. Psychotropic medications were independently associated with falls [IRR 1.15 (95% CI 1.00-1.31)] and unexplained falls [IRR 1.46 (95% CI 1.20-1.78)]. Taking ≥ 2 psychotropic medications was further associated with future fracture (IRR 1.47 (95% CI 1.06-2.05)]. Antidepressants were independently associated with falls [IRR 1.20 (1.00-1.42)] and unexplained falls [IRR 2.12 (95% CI 1.69-2.65)]. Anticholinergics were associated with unexplained falls [IRR 1.53 (95% CI 1.14-2.05)]. 'Z'-drug and benzodiazepine use were not associated with falls or fractures. Conclusion: Psychotropic medications, particularly antidepressants and anticholinergic medications, are independently associated with falls and fractures. Regular review of ongoing need for these medications should therefore be central to the comprehensive geriatric assessment.
PUBLISHED
Keywords: Antidepressant, Antidepressants, Falls, Fractures, Older, Psychotropic; Ageing